1998
DOI: 10.1042/bj3320173
|View full text |Cite
|
Sign up to set email alerts
|

Platelet sarco/endoplasmic reticulum Ca2+ATPase isoform 3b and Rap 1b: interrelation and regulation in physiopathology

Abstract: Platelet Ca2+ signalling involves intracellular Ca2+ pools, whose content is controlled by sarco/endoplasmic reticulum Ca2+ATPases (SERCAs). Among these, a key role is played by the inositol trisphosphate-sensitive Ca2+ pool, associated with the SERCA 3b isoform. We have investigated the control of this Ca2+ pool through the cAMP-dependent phosphorylation of the GTP-binding protein, Rap (Ras-proximate) 1b. We first looked for this Ca2+ pool target of regulation by studying the expression of the different SERCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…This result is compatible with recent evidence that extracellular stimuli inducing T lymphocyte adhesion via LFA-1, such as T cell receptor stimulation and phorbol esters, do so by inducing an influx of extracellular calcium (28). Although in several studies Rap1 has been implicated in the regulation of cellular calcium levels (35)(36)(37), clear evidence is still lacking. A recent study demonstrated that Rap2b via interaction with phospholipase C⑀ is able to regulate intracellular calcium signaling in HEK293 cells (38).…”
Section: Discussionsupporting
confidence: 88%
“…This result is compatible with recent evidence that extracellular stimuli inducing T lymphocyte adhesion via LFA-1, such as T cell receptor stimulation and phorbol esters, do so by inducing an influx of extracellular calcium (28). Although in several studies Rap1 has been implicated in the regulation of cellular calcium levels (35)(36)(37), clear evidence is still lacking. A recent study demonstrated that Rap2b via interaction with phospholipase C⑀ is able to regulate intracellular calcium signaling in HEK293 cells (38).…”
Section: Discussionsupporting
confidence: 88%
“…These findings are in correspondence with the hypothesis that Rap1 is a molecular "switch" that regulates SERCA activity: the cAMP-induced Rap1 activation is correlated with the inhibition of SERCA and a rise in [Ca 2ϩ ] i (present data), and the PKA-mediated phosphorylation of Rap1 relieves the inhibition, resulting in activation of Ca 2ϩ -ATPases and a decrease in [Ca 2ϩ ] i . 10,11 The latter property is also observed in Ca 2ϩ regulation by phospholamban in cardiac and muscle cells. 23,24 Phosphorylation of this 24-kDa protein by PKA triggers stimulation of cardiac sarcoplasmic reticulum Ca 2ϩ -ATPases, leading to a fall in [Ca 2ϩ ] i .…”
Section: Camp-induced Rap1 Activation Is Not Accompanied By Phosphorymentioning
confidence: 87%
“…Two types of cAMP GEF for Rap1 have been reported: cAMP-GEF-I, also called exchange protein, directly activated by cAMP (Epac), and cAMP-GEF-II. Interestingly, earlier work by Corvazier et al 11 and LacabaratzPorret et al 10 indicated that Rap1 might be involved in Ca 2ϩ regulation in platelets. First, proteins in crude platelet plasma membrane vesicles, ranging in molecular mass from 22 to 29 kDa, bound GTP␥S.…”
Section: Camp-induced Rap1 Activation Is Not Accompanied By Phosphorymentioning
confidence: 99%
See 1 more Smart Citation
“…In this mode, cAMP promotes Ca 2ϩ release through RY receptor as a consequence of increased filling of the ER by a mechanism that involves cAMP-regulated guanine nucleotide exchange factor and its interaction with Rap1b (26,69). There is no consensus as to the consequences of phosphorylation of IP 3 Rs in terms of Ca 2ϩ release.…”
Section: Regulation Of Ry Receptors By Second Messengersmentioning
confidence: 99%